PENGARUH TUJUAN PENGGUNAAN ANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN PARTISIPASI ANGGARAN DAN PENEKANAN ANGGARAN SEBAGAI VARIABEL MEDIASI - Yeyen Pratiwi; Lisa Martiah Nila Puspita (Jurnal Akuntansi, 2017)
This study to examine the effect of purpose of budget use on the budgetary slack, where budget participation and budget emphasis as a mediating variable. The sample in this study was 70 managers consisting of the financial managers, marketing managers and other managers. This study is an empirical research with quantitative approach using primary data. The analytical tool used in this research is descriptive and inferential statistics with SmartPLS version 3.0. This results of this study indicate that the purpose of budget use has a positif effect on budgetary slack. The effect of purpose of budget use on budgetary slack also positively mediated by budget participation and budget emphasis.Keyword: Purpose of Budget Use, Budgetary Slack, Budget Participation, Budget Emphasis